2009
DOI: 10.1097/tp.0b013e3181b2fd83
|View full text |Cite
|
Sign up to set email alerts
|

Donor HO-1 Expression Inhibits Intimal Hyperplasia in Unmanipulated Graft Recipients: A Potential Role for CD8+ T-Cell Modulation by Carbon Monoxide

Abstract: Organs expressing cytoprotective HO-1 have a direct influence on the recipient immune response. Given the important role of CD8 T cells and IFN-gamma in chronic rejection, these data suggest that donor HO-1 expression may be useful to augment other immunosuppressive therapies to prolong graft survival and inhibit intimal hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…Briefly, the tissue was mashed through a 40-μm also been reported, which reduces rejection of organ transplants (81,82). In the present study, we showed that the generation of CD8 + CD122 + T cells with regulatory function was dependent on Hmox1 expression in mice.…”
Section: Cell Preparationssupporting
confidence: 52%
“…Briefly, the tissue was mashed through a 40-μm also been reported, which reduces rejection of organ transplants (81,82). In the present study, we showed that the generation of CD8 + CD122 + T cells with regulatory function was dependent on Hmox1 expression in mice.…”
Section: Cell Preparationssupporting
confidence: 52%
“…10 Because this "single-hit" mechanical injury model has few clinical counterparts, we have continued this work using mouse aortas across a full major histocompatibility complex mismatch (H-2 d to H-2 b ) without immunosuppression, a model that involves rapid destruction of the endothelium of transplanted allografts and continuous immune-mediated damage to the donor vessel resulting in IH within 4 to 6 weeks. 12 …”
Section: See Accompanying Article On Pagementioning
confidence: 99%
“…12 Briefly, a 5-mm segment of infrarenal donor aorta, flushed with heparin, was transplanted into recipient aorta. Blood flow was confirmed by direct inspection after the clamps were removed.…”
Section: Aortic Transplantationmentioning
confidence: 99%
“…It is essential to determine whether restricting the expression of HO-1 exclusively to the transplanted organ can prevent graft rejection and thereby enhance the survival of the recipients. It has recently been reported that donor expression of HO-1 induced by hemin inhibited intimal hyperplasia of aorta in unmanipulated graft recipients by modulating CD8 þ cells [16]. However, in this study, the inducer was systemically administered, resulting in widespread but only transient expression of HO-1 in donors.…”
Section: Introductionmentioning
confidence: 82%
“…To date, the methods commonly employed to induce HO-1 expression cause widespread expression of HO-1 in the tissues of the transplant recipients [16]. It is essential to determine whether restricting the expression of HO-1 exclusively to the transplanted organ can prevent graft rejection and thereby enhance the survival of the recipients.…”
Section: Introductionmentioning
confidence: 99%